ANALISIS LINE BALANCING PADA PRODUKSI SETRIKA DI PT PHILIPS INDUSTRIES BATAM - Dian Pratiwi; Elsya Paskaria Loyda Tarigan (Computer Science and Industrial Engineering, 2025)
This study discusses line balancing in the production of irons at PT Philips Industries Batam, aiming to improve efficiency by addressing bottlenecks in the manufacturing process. The main focus is to optimize task distribution across workstations to minimize non-value-added time and enhance production line performance. Before the improvements, line efficiency was recorded at 94%, but there was still considerable idle time. Data collection was conducted through direct observation and time measurement of 18 operations using the Ranked Positional Weight (RPW) method. The analysis revealed that the implementation of Unique Device Identifier (UDI) labels led to increased operational times, particularly in operations 11, 15, and 18, causing workflow delays. After applying line balancing strategies, efficiency significantly improved from 67.97% to 96.23%. This study demonstrates that better task distribution can reduce production delays and support the achievement of operational targets. Key improvements include a reduction in balance delay and a smoother production flow, resulting in increased overall productivity. These findings highlight the importance of line balancing in optimizing manufacturing performance and provide valuable insights for industries seeking to enhance competitiveness through a more efficient production system.